2009
DOI: 10.1038/hr.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus accelerates left ventricular diastolic dysfunction through activation of the renin–angiotensin system in hypertensive rats

Abstract: Diabetes mellitus (DM) is a major risk factor for heart failure, independent of coronary artery disease or hypertension (HT). Therefore, our study was designed to examine the mechanisms of DM-induced left ventricular (LV) diastolic dysfunction. In this study, we made five different 10-week treatment groups of Dahl salt-sensitive rats as follows: Control; a low-salt (0.5% NaCl) diet, HT; a high-salt (5% NaCl) diet, DM; a low-salt diet with streptozotocin (STZ) injection (30 mg kg À1 i.p.), HT+DM; a highsalt die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 53 publications
2
18
1
2
Order By: Relevance
“…40 In combination with hypertension, Fukui et al 41 observed that DM accelerates LV diastolic dysfunction via renin-angiotensin system in hypertensive rats. Taken together, hypertension and DM could synergistically deteriorate diastolic function in human.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…40 In combination with hypertension, Fukui et al 41 observed that DM accelerates LV diastolic dysfunction via renin-angiotensin system in hypertensive rats. Taken together, hypertension and DM could synergistically deteriorate diastolic function in human.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…To determine myocyte cross-sectional area (CSA), 30 cardiomyocytes were traced in each section in the slides stained with HE using NIH Image software. The percentage area of perivascular and interstitial fibrosis in the LV at the papillary muscle level in the slides stained with MT and SR was determined (6,8). The remaining LV was immediately placed in liquid nitrogen and stored at Ϫ80°C for Western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…LV ejection fraction and relative wall thickness were calculated as previously described. 22 LV diastolic function was assessed by the measurement of LV transmitral early peak flow velocity (E) to LV transmitral late peak flow velocity (A) wave ratio (E/A ratio). 22 …”
Section: Echocardiographymentioning
confidence: 99%